(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
Using more than one motor in an EV (Electric Vehicle) powertrain enhances the vehicle’s torque, acceleration, and speed capabilities. A more tractive force produced by the electric powertrain requires more electric current from the battery. In modern EVs, mechanical power production can be approached to the wheels reducing the mechanical losses in the transmissions. It is the case with multiple-motor powertrains. Several advantages regarding vehicle control, physical performance, and energy efficiency improvement are obtained. In the current study, a BLDC (brushless dc) motor is investigated from the efficiency point of view to build a multiple-motor powertrain. A new methodology uses analytic calculations, simulations, and physical measurements. A powertrain with three identical motors results in a new vehicle configuration. Each motor’s energy consumption improvements are analyzed following a normalized testing procedure. The results are compared with those of a single-motor powertrain.